TECHNICAL EFFICIENCY AND PRODUCTION FACTORS OF RAINFED RICE FARMING IN SOUTH SULAWESI - Junaedi Junaedi; Arifin Arifin; La Sumange La Sumange; Muhammad Arsyad Biba; Zulkifli Zulkifli (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Efficiency in the use of production factors is an indication of the success and sustainability of a farm. If farming has been done efficiently and at a certain level of input, then production will be optimal and maximum profit will be obtained. The allocation of efficient and effective use of production factors will determine the achievement of farming efficiency. The objective of this research is to analyze the technical efficiency of rainfed rice farming and to analyze the factors that affect the production of rainfed rice farming. Data were collected from rice farmers in Maros and Pangkep Regency, 100 farmers were taken as respondents using a multi-stage cluster random sampling technique. The analysis used is descriptive quantitative to measure technical efficiency and multiple regression for factors that affect the production of rainfed rice farming. The results showed that rainfed lowland rice farming in South Sulawesi is not yet technically inefficient. The average technical efficiency value obtained is 0.77 or 77%, meaning that farmers have the opportunity to increase their technical efficiency value to get higher yields of 16.91%. The factors that significantly affect the production of rainfed lowland rice farming in South Sulawesi are land area, number of seeds, amount of fertilizer, and amounts of pesticides.